2022
DOI: 10.1111/jonm.13555
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nurse staffing on falls performance within a health care system: A descriptive study

Abstract: Aim:The purpose of this study was to examine the impact of nurse staffing on inpatient falls performance across a multi-hospital system.Background: Evidence to support which staffing variables influence fall performance so that health care organizations can better allocate resources is lacking.Method: A descriptive study design was used to analyse the impact of nurse staffing and falls performance, with units dichotomized as either high or low performing based on national benchmarking data. The impact was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Furthermore, hospital-acquired adverse events have been shown to be sensitive to staffing ratios and composition, specifically among nurses . Given that private equity firms have reduced staffing and changed the clinician labor mix at acquired hospitals and clinics, an analogous cost-cutting strategy in our sample may help explain the increase in hospital-acquired conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, hospital-acquired adverse events have been shown to be sensitive to staffing ratios and composition, specifically among nurses . Given that private equity firms have reduced staffing and changed the clinician labor mix at acquired hospitals and clinics, an analogous cost-cutting strategy in our sample may help explain the increase in hospital-acquired conditions.…”
Section: Discussionmentioning
confidence: 97%
“…An explanation for this could be the unequal distribution of resources, such as staff, nurses, and equipment, among different shifts. This imbalance is likely to impact the occurrence of falls in each shift, as the availability and utilization of resources could affect patient safety and care quality [33] [34] [35]. The study found that medication involvement was closely related to fall risk levels during the morning shift, emphasizing the importance of investigating the type of medication involved.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital-acquired adverse events have been shown to be sensitive to staffing ratios and staff composition. 8 Private equity firms are known to decrease staffing and staff skill mix upon acquisition to decrease cost. The results of this well-designed study should raise many questions regarding operational motives and clinical outcomes of private equity firm ownership of hospitals and outpatient centers.…”
Section: Quality Of Care In Hospitals Owned By Private Equity Firmsmentioning
confidence: 99%
“…Medicare beneficiaries treated at the private equity–owned hospitals experienced a reduction in discharges home of 0.6% compared with those treated at the control group hospitals. Hospital-acquired adverse events have been shown to be sensitive to staffing ratios and staff composition 8 . Private equity firms are known to decrease staffing and staff skill mix upon acquisition to decrease cost.…”
Section: Quality Of Care In Hospitals Owned By Private Equity Firmsmentioning
confidence: 99%